Theōsis: A Comparative Study of T. F. Torrance and Rāmānuja - Tsoukalas, Steven (Journal of Hindu-Christian studies, 2017)
This essay is an imaginative conversation as I engage two religious thinkers-the prolific Reformed theologian Thomas F. Torrance (1913-2007) and the great Vedāntin Rāmānuja (traditionally, 1017-1137). I will compare Torrance's theology of theosis (participation in the life of God) and theoria (contemplation as a way of participation in the life of God) with those of Rāmānuja. Though the words themselves were likely unknown to Rāmānuja, through his works one can see a notion of theōsis.